(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Methotrexate is folic acid antagonist, used in the therapy of various types of diseases. Oxidative stress and inflammation have the major role in methotrexate toxicity. Objective:To study the protective effects of felodipine against methotrexate-induced hepatotoxicity in rabbits. Methods:Twenty four rabbits divided randomly into three groups. Group I was left without treatment, group II received a dose of 20 mg/kg methotrexate (MTX) intraperitoneally from 3rd day for three successive days and group III received a dose of 0.5 mg/kg felodipine orally for 7 days in addition to MTX therapy similar to group (2). On 8th day the following parameters (liver enzymes, liver tissue homogenate of glutathione, malondialdehyde and tumor necrosis factor-?) were monitored. As well as assessment of histological changes on liver tissue sections after scarification. Results:Administration of felodipine significantly decreased the elevated levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), malondialdehyde and tumor necrosis factor-alpha. It also elevated glutathione levels significantly, with improvement of histological features related to MTX exposure in group III compared with group II. Conclusion: Felodipine can protect hepatic tissue against MTX-induced hepatotoxicity. Keywords: Hepatotoxicity, Methotrexate, Felodipine, Glutathione, Malondialdehyde, Tumor Necrosis Factor-alpha.